1927 Ind. Acts 469, Public Offenses — Ownership, Possession or Control of Machine Guns or Bombs — Penalty, ch. 156, § 1 - (:unkn) unknown (General Publisher, 1927)
Prohibited owning or possessing a machine gun or bomb in an automobile. Punishable by imprisonment for 1-5 years.
--
Keywords: MACHINE GUN RESTRICTION